RÉHABILITATION PAR l’ATRIPLEX DES PARCOURS STEPPIQUES DU SUD DE LA PREFECTURE DE SAÏDA (ALGERIE OCCIDENTALE) - Bessaih Abderrahmane; Hellal Benchaben; Ayad Nadira (European Scientific Journal, ESJ, 2014)
Algerian steppe area subject to desertification is crowded with sheep population. Overgrazing is one of the causes of desertification of steppe rangelands. It is one of the phenomena preventing the reconstitution of steppe rangelands. Long periods of drought and sedentary herds have weakened the regeneration of steppe rangelands. A new approach is proposed for the rehabilitation of degraded grassland ranges with Atriplex canescens. This is a promising approach for rangeland rehabilitation suffering from overuse. Atriplex canescens, famous for its high forage value, is highly valued by sheep. The use of rehabilitated, with a mode of rotational grazing or controlled grazing (set off) pathways is a form of struggle against the exploitation and thus desertification. This study reveals the successful rehabilitation of degraded grassland ranges.